The Multiplier Effect in Two-Sided Markets with Bilateral Investments - Deniz Dizdar; Benny Moldovanu; Nora Szech (Center for Economic Studies and ifo Institute (CESifo), 2017)
Agents in a finite two-sided market are matched assortatively, based on costly investments. Besides signaling private, complementary types, investments generate direct benefits for partners. We explore quantitative properties of the equilibrium investment behavior. The bilateral external benefits induce an investment multiplier effect. This multiplier effect depends in a complex way on agents' uncertainty about their own rank and about the types and investments of potential partners. We characterize how the multiplier effect hinges on market size, and how it interacts with other important factors such as the costs of investment and the signaling incentives induced by competition.
Keywords: C78; D44; D82; 330; matching; signaling; investment; multiplier effect